A girl named Rosita : the story of Rita Moreno: actor, singer, dancer, trailblazer! - Denise, Anika (Harper, an Imprint of HarperCollinsPublishers, 2020)
"The life of Puerto Rican actress, dancer, and singer Rita Moreno, from her girlhood journey to the United States to her rise as a timeless superstar"--